Identification of Polymorphism in Exons 8 and 13 of Lactoferrin Gene in Murrah Buffalo - Dinesh, Krishanender; Verma, Archana; Gupta, Ishwar Dayal (Indian Journal of Dairy Science, 2021)
Lactoferrin is one of the important candidate genes for mastitis resistance in dairy animals. The gene is located on chromosome BBU21 and consists of 17 exons spanning over 32.95 kb of genomic DNA. The present study was undertaken with the objectives to identify allelic variants in exon 8 and 13 of lactoferrin gene and to analyze their association with incidence of clinical mastitis in Murrah buffalo. A total of 200 lactating Murrah buffaloes, grouped as mastitis affected and non-affected, were included in the study. Genomic DNA was isolated from the whole blood sample of each animal. Two primer sets were used to amplify exon 8 and 13 of lactoferrin gene, which yielded respective amplicons of 216 bp and 211 bp. The PCR-RFLP analysis of lactoferrin gene revealed monomorphic pattern in exon 8 and polymorphic pattern in exon 13. Hpy 188I-RFLP for exon 13 exhibited polymorphism with three genotypes: AA, AB and BB with respective frequencies of 0.20, 0.58 and 0.22 whereas, frequencies for A and B alleles were estimated as 0.49 and 0.51. Comparison of nucleotide sequence of exonic region of lactoferrin gene in Murrah buffalo with that of Bos taurus cattle revealed a total of 5 mutations out of which 2 were transition and 3 were transversion. The SNPs in exon 8 were found to be non synonymous and revealed two amino acid changes in exon 8 of Murrah buffalo as compared to Bos taurus cattle. Chi-square (Ï‡2) analysis indicated non significant association between genetic variants of exon 13 and incidence of clinical mastitis.